PENERAPAN MEDIA PEMBELAJARAN BERBASIS PANCA INDERA (MULTISENSORI) UNTUK MENINGKATKAN EFEKTIVITAS BELAJAR PESERTA DIDIK - Ainiyah, Zainabul; Ainul Yaqin , Firdaus; Fitri Amalia , Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Instructional media play a strategic role in enhancing the effectiveness of the teaching and learning process in Islamic elementary schools (madrasah ibtidaiyah). A multisensory approach, which engages various senses, is considered to strengthen students’ understanding by providing richer learning experiences. This study aims to describe the forms of collaboration between teachers and PGMI (Islamic Elementary Teacher Education) students in developing multi-sensory learning media, to analyze its implementation in the classroom, and to measure its effectiveness in improving students’ learning quality at MI Sunan Bonang II. This research employed a descriptive qualitative approach with a field study design. The participants consisted of classroom teachers PGMI students, MI students, and the school principal as supporting informants. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using Miles and Huberman’s interactive model, which includes data reduction data display, and conclusion drawing. Data validity was ensured through triangulation of sources, techniques, and time. The findings indicate that, first, collaboration between teachers and PGMI students occurred in three main stages: planning, implementation, and evaluation of the media. Second, the implementation of multi-sensory media integrated visual, auditory, and kinesthetic elements, creating more interactive and engagingclassroom activities while accommodating different learning styles. Third, the effectiveness of the media was reflected in improved student concentration, comprehension, motivation, academic achievement, and a more conducive classroom atmosphere. In conclusion, this study highlights that collaboration between teachers and PGMI students produces innovative and contextually relevant multi-sensory learning media, which significantly contribute to enhancing the quality of education in madrasah ibtidaiyah.